(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To describe the knowledge regarding safe injection practices, prevention of sharp injuries and medical waste management in Nursing students of the University of Medicine and Pharmacy at Ho Chi Minh City. Method: A cross-sectional study conducted in 264 Nursing students, during the academic year 2022-2023. A pre-designed questionnaire was used to survey knowledge regarding standard precautions. Results: The study found that 51% of nursing students possessed accurate knowledge regarding safe injection practices and the prevention of injuries from sharp objects. Notably, the aspect concerning contact precautions for managing wounds in HIV/AIDS patients had the highest correct response rate at 92.1%. Additionally, 73% of nursing students demonstrated correct knowledge about medical waste management, with the highest accuracy (93.2%) in the area of waste segregation at the point of generation. Conclusion: Overall, more than half of the students have correct knowledge about safe injection practices, prevention of sharp injuries, and medical waste management in standard precautions (all above 50%).